Taxonomy of the leafhopper genus Limentinus (Hemiptera: Cicadellidae: Coelidiinae) with description of three new species from Madagascar - Jin, Mengyuan; Yang, Li; Cao, Yanghui; Zhang, Yalin (Zootaxa, 2026)
The leafhopper genus Limentinus is reviewed and three new species, Limentinus anja, L. isomerus and L. sextaspina spp. nov. from Madagascar are described and illustrated. Species checklist, key to males and aedeagus illustrations to all known species of Limentinus are given. The mitochondrial cytochrome c oxidase subunit I (COI) sequences from the latter two species are provided.